Prevalence of depression and anxiety among elderly primary care patients in Palestine - Maraqa, Beesan Nader; Nazzal, Zaher; Hamshari, Suha; Alutt, Barlant; Rishmawi, Ekram; Qawasmeh, Abdallah (Frontiers in Psychiatry, 2024)
Background and objectives : Depression and anxiety are common mental health disorders among the elderly worldwide. In this study, we estimated the prevalence of depression and anxiety and related risk factor among elderly attending Primary Health care ( PHC) centers in Palestine.A cross-sectional study was conducted from February to July 2021 with a sample size of 380 participants aged ≥60 attending PHC centers in West Bank, using an interviewer-administered questionnaire. We used the Geriatric Depression Scale-15 and the Geriatric anxiety Scale to screen for depression and anxiety, respectively. Logistic regression models were used to identify predictors of depression and anxiety.The prevalence of depression and anxiety was 41.1% and 39.2%, respectively. Elderly people living in rural areas (aOR= 2.63; 95%CI: 1.72-4.20), uneducated (aOR= 2.92; 95%CI: 1.41-6.13), and without monthly income (aOR= 3.42; 95%CI: 1.52-7.61) were more likely to have depression. On the other hand, anxiety was independently associated with living in rural areas (aOR= 1.93, 95%CI: 1.23-3.04) and having non-communicable diseases (aOR= 2.01; 95%CI: 1.13-3.49).Depression and anxiety are common in Palestine, a developing country with a lack of elderly related services. This should be emphasized at the national and regional levels where geriatric health care services are scarce. Such information is required by policymakers and external funding agencies in order to develop future agendas